2001
DOI: 10.1557/proc-703-v3.10
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Traditional Vapor-Liquid-Solid Method for Bulk Synthesis of Semiconductor Nanowires

Abstract: Multiple silicon nanowires were synthesized using large gallium pools and microwave plasma. Results showed that nanowires growing out of different sized large gallium drops show little variation in diameters, suggesting that our non-traditional technique can be used to synthesize bulk amounts of monodispersed nanowires out of thin films of molten gallium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In the case of silicon dissolution from the solidliquid interface, the temperature is the single most important parameter for determining the rate at which the dissolution occurs. Due to large differences in melting point of solid silicon and the Ga-Si eutectic temperature (∼30 • C), the dissolution is quite rapid even at modest temperatures of few hundred • C. Later, we showed that chemical vapour transport of silicon using atomic hydrogen onto molten gallium placed on non-silicon substrates confirmed that silicon could be dissolved directly from the gas phase into molten gallium for silicon nanowire synthesis [7]. Here, we report our experiments using silane directly in the gas phase for bulk synthesis of silicon nanowires from molten gallium covered non-silicon substrates.…”
Section: Introductionmentioning
confidence: 75%
“…In the case of silicon dissolution from the solidliquid interface, the temperature is the single most important parameter for determining the rate at which the dissolution occurs. Due to large differences in melting point of solid silicon and the Ga-Si eutectic temperature (∼30 • C), the dissolution is quite rapid even at modest temperatures of few hundred • C. Later, we showed that chemical vapour transport of silicon using atomic hydrogen onto molten gallium placed on non-silicon substrates confirmed that silicon could be dissolved directly from the gas phase into molten gallium for silicon nanowire synthesis [7]. Here, we report our experiments using silane directly in the gas phase for bulk synthesis of silicon nanowires from molten gallium covered non-silicon substrates.…”
Section: Introductionmentioning
confidence: 75%
“…The ethanolic suspension was then dripped on a carbon coated copper TEM grid. The chemical composition was investigated by secondary ion mass spectroscopy (SIMS) [CAMECA] using Ar 1 ions analyzing the isotopes C 12 , N 14 , O 16 , Al 27 and Ga 69 . Rutherford backscattering spectroscopy (RBS) measurements were taken using the instruments at the DTL (Dynamic Tandem Laboratory).…”
Section: Methodsmentioning
confidence: 99%
“…The diameters of the reported GaN nanostructures varied widely with the synthesis method but were within the range of 50 nm. 2,3,14,16,17,46 Nanostructures with bigger diameters have also been reported, 24,25,45 however, nanostructures with very small diameters of a few nm have not been routinely achieved. In all cases lengths were of the order of several microns.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…Our work has proved that one can successfully obtain high densities of nanometer scale nuclei from pools of quasi-miscible solvents for solutes. [12][13] The critical nucleus diameter, d c , associated with the creation of a nucleus from a molten solvent according to classical nucleation theory is given by (Eq. 1), 14…”
Section: Multiple Nucleation and Growth Of Nanowires Using Low-meltinmentioning
confidence: 99%